FRI0130 Efficacy of A Comprehensive Cardiovascular Risk Reduction Patient Education Programme in Patients with Early Inflammatory Arthritis Following A Treat To Target Therapeutic Regime. (15th July 2016) - Inomata, H.; Bissell, L.-A.; Naraghi, K.; Nam, J.; Burska, A.; Hensor, E.; Emery, P.; Buch, M.; Andrews, J.
Abstract : Background: Evidence suggests cardiovascular disease (CVD) risk in patients (pt, pts) with Inflammatory arthritis (IA), Rheumatoid arthritis (RA) is equivalent to that of type II diabetes mellitus 1 . The accepted guidance is lifestyle factor modifications should be addressed in IA 2, but little is known of the impact of CVD risk reduction pt education programmes delivered to pts with IA within a Rheumatology service setting. Objectives: To describe the utility of a comprehensive CVD risk reduction pt education programme in pts with newly diagnosed IA following a treat to target standard therapeutic regime. Methods: 387 pts with IA (RA and Undifferentiated Inflammatory Arthritis: UIA) were assessed at baseline (BL) for CV risk factors (RFs) (see Table 1 ) Pts were; RA; pts (1987 or 2010 ACR criteria) (n=237) and UIA; pts not meeting ACR RA criteria (n=150). A standardized co-morbidity pt education programme, which included CVD risk reduction, was delivered throughout the first 12 months (M). The impact on modifiable CVD RFs was assessed at 12M. Results: 108 RA, 34 UIA pts had complete datasets (see Table 1 ). Of those smoked at BL, 15% reported being ex-smokers at 12M and the number smoked had decreased in 44%. 10% who reported being ex-smokers at BL altered their status to never having smoked by 12M and their reported number previously smoked reduced by 43% at 12M. Alcohol use reduced in 39% and increased in 24% (overall decrease, p=0.033). At BL, 56% of pts reported doing no moderate exercise at all; at 12M around a third of the pts had either increased or decreased the amount of exercise (no overall change). Disease activity generally decreased (p<0.001) and mobility increased (p=0.004). Conclusions: A significant reduction in alcohol units and improvement in smoking habits were seen. However, despite significant improvements in IA disease activity and mobility, there was no improvement in exercise from the low level reported at BL. The need to address modifiable CVD RFs in IA is widely accepted by Rheumatologists but effecting lifestyle change is challenging. Behavioural change in exercise is complex, particularly in chronic disease. Further studies are required to optimise the approach in IA. References: Ann Rheum Dis 2009; 68:1395–1400 ARD 2010; 69:325–331 Disclosure of Interest: None declared